2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC) 2015
DOI: 10.1109/pvsc.2015.7356176
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of the influence of string mismatch on the yield of PV modules augmented by static planar reflectors

Abstract: Abstract-Photovoltaic (PV) modules are generally installed by the application of empirical rules aimed at reducing shadows during the periods of high solar irradiation. A traditional installation on a horizontal surface results in largely spaced rows of modules with a relatively low tilt angle. The addition of inter-row reflectors results in more direct and diffuse flux transmitted to the cells. The "Aleph" (Amélioration de l'Efficacité Photovoltaïque) project aims to define clear rules for optimal settings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Some studies have revealed that a vertical PV module with a horizontal planar concentrator is the best position at high latitudes (Duffie et al, 2020). Pavlov et al (2015), revealed that using planar concentrators increased daily power by 35% during cloudless days at specified times of the year. Bahaidarah et al (2013), developed a solar system that is cooled by the flow of water on the backside of the PV module in the Al-Dhahran (KSA) climatic condition.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have revealed that a vertical PV module with a horizontal planar concentrator is the best position at high latitudes (Duffie et al, 2020). Pavlov et al (2015), revealed that using planar concentrators increased daily power by 35% during cloudless days at specified times of the year. Bahaidarah et al (2013), developed a solar system that is cooled by the flow of water on the backside of the PV module in the Al-Dhahran (KSA) climatic condition.…”
Section: Introductionmentioning
confidence: 99%
“…This model is called the single-diode model [4]- [12] with five modeling parameters: light-induced current I L , diode dark saturation current I s , diode quality factor m, series resistance R s , and shunt resistance R sh . Another diode, when added in parallel to the first diode, models the effect of recombination in the junction space charge region and is called the double-diode model [13]- [16]. Introduction of the second diode adds two additional parameters, namely the diode quality factor m 2 and the dark saturation current I s 2 .…”
Section: Introductionmentioning
confidence: 99%